1993
DOI: 10.1159/000126354
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Central Cholinergic Muscarinic Receptors and Histamine H<sub>1</sub> Receptors in Hyperglycemia Induced by Prostaglandin F<sub>2</sub>α in Rats

Abstract: We studied the effects of the histamine H1 receptor antagonists diphenhydramine and pyrilamine, the H2 receptor antagonist ranitidine and the muscarinic receptor antagonist atropine injected into the third cerebral ventricle on prostaglandin F2α (PGF2α)-induced hyperglycemia in anesthetized fed rats. The concomitant injection of diphenhydramine (1 × 10–8, 5 × 10–8 mol) with 50 µg PGF2α significantly suppressed the increase in hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Subsequent studies revealed that hyperglycemia induced by injection of PGF2α into the ventricle is as a result of an increase in epinephrine secretion from the adrenal medulla, muscarinic receptors of cholinoceptive neurons and, in part, by H1 receptors in the central nervous system. [97] , [98] ). These studies suggest that PG system plays a role in the development of hyperglycemia both by peripheral (by inducing inflammation and insulin resistance) and by central actions.…”
Section: Ageing Pg System Hyperglycemia Oxidative Stress and Telomentioning
confidence: 99%
“…Subsequent studies revealed that hyperglycemia induced by injection of PGF2α into the ventricle is as a result of an increase in epinephrine secretion from the adrenal medulla, muscarinic receptors of cholinoceptive neurons and, in part, by H1 receptors in the central nervous system. [97] , [98] ). These studies suggest that PG system plays a role in the development of hyperglycemia both by peripheral (by inducing inflammation and insulin resistance) and by central actions.…”
Section: Ageing Pg System Hyperglycemia Oxidative Stress and Telomentioning
confidence: 99%